Diversity change during the rise of tetrapods and the impact of the ‘carboniferous rainforest collapse’ - Dunne, Emma; Close, Roger A.; Button, David J.; Brocklehurst, Neil; Cashmore, Daniel D.; Lloyd, Graeme T.; Butler, Richard J. (Proceedings of the Royal Society of London, Series B: Biological Sciences, 2018)
The Carboniferous and early Permian were critical intervals in the diversification of early four-limbed vertebrates (tetrapods), yet the major patterns of diversity and biogeography during this time remain unresolved. Previous estimates suggest that global tetrapod diversity rose continuously across this interval and that habitat fragmentation following the ‘Carboniferous rainforest collapse’ (CRC) drove increased endemism among communities. However, previous work failed to adequately account for spatial and temporal biases in sampling. Here, we reassess early tetrapod diversity and biogeography with a newglobal species-level dataset using sampling standardization and network biogeography methods. Our results support a tight relationship between observed richness and sampling, particularly during the Carboniferous. We found that subsampled species richness initially increased into the late Carboniferous, then decreased substantially across the Carboniferous/Permian boundary before slowly recovering in the early Permian. Ouranalysis of biogeography does not support the hypothesis that theCRCdrove endemism; instead, we found evidence for increased cosmopolitanismin the early Permian. While a changing environment may have played a role in reducing diversity in the earliest Permian, our results suggest that the CRC was followed by increased global connectivity between communities, possibly reflecting both reduced barriers to dispersal and the diversification of amniotes.
Created from Fastlane, Scopus look-up
Keywords: Biogeography; Carboniferous rainforest collapse; Diversity; Palaeozoic; Sampling; Tetrapoda